Global stability in spite of ''local instability'' with learning - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2000)
We analyse learning dynamics in deterministic economies when agents generate their forecasts by performing least squares regressions on lagged values of the endogenous state variable. We establish conditions for the global convergence to the deterministic steady state of the dynamics under learning. Our global stability result is particularly relevant since the learning rules we consider are already known to produce locally divergent behaviour around the steady state.